Strategies to maintain market access for pork and enhance functionality of beef proteins - Cochran, Hannah, author; Martin, Jennifer, advisor; Bosco-Lauth, Angela, committee member; Garry, Franklyn, committee member; Roman-Muniz, Noa, committee member (Colorado State University. Libraries, 2023)
African swine fever is a high-consequence foreign animal disease endemic to sub-Saharan Africa and the island of Sardinia. The U.S. is the world's third largest pork producer, and ASF introduction would severely disrupt the pork supply chain, emphasizing a need to protect market access for U.S. proteins. However, niche producers raising swine intended for exhibition may not follow stringent biosecurity protocols and livestock show circuits may promote untracked animal movement across the country, potentially exacerbating virus spread in the event of ASF incursion into the U.S. Two Qualtrics surveys designed to evaluate knowledge, understanding, and perceptions of ASF and biosecurity principles of youth swine exhibitors and adults involved in the exhibition swine industry were distributed via flyers, emails, and canvassing at livestock shows. Youth exhibitors (age 21 and under) answered questions assessing their knowledge and provided basic demographic information, including their home state and states to which they traveled for exhibitions. Adult respondents answered the same questions assessing their knowledge and provided information on their time involved in the swine industry and number of shows attended by the youth they advise (if any). Youth respondents (n = 127) lived in 14 states and exhibited in 23 states, with 35% and 28% holding membership in state and national swine organizations, respectively. When provided with a list of ASF clinical signs, 34 individuals (26.9%) correctly identified all symptoms. Twenty-nine individuals (23%) incorrectly responded that ASF has been found in the U.S., and ten (7.9%) believed the virus cannot spread between pigs. Increased biosecurity understanding in youth exhibitors showed a significant relationship with an increase in years involved (p<0.05). Adult respondents (n = 211) had been involved in the swine industry for an average of 21 years, and the youth they advised attended 14 exhibitions in an average year. Nearly all adults (90.5%) identified direct contact with infected animals as a method of ASF transmission, while far fewer (36.39%) identified animal feed as a possible mechanism of transmission. These responses indicate highly varied knowledge of symptoms, routes of transmission, and biosecurity recommendations. Youth membership in state or national swine organizations offers a route for outreach and educational activities to enhance foreign animal disease preparedness, and adult presence at swine exhibitions allows for a wide variety of programming for all ages to better serve all levels of understanding. Fluctuations in the beef supply chain due to COVID-19 triggered discussions on methods to fully utilize edible proteins from beef carcasses, such as collagen. One potential method is the addition of collagen powder to beef frankfurters to replace a fraction of lean grind. The inclusion of NOVAPRO® collagen powder to beef franks at three hydration levels resulted in no significant differences (p>0.05) in water activity, pH, or shear force values between the treatment groups. Additionally, trained sensory panelists did not discern differences between treatment or control samples when asked to rate attributes that included beef flavor intensity, seasoning intensity, springiness, and mouth coating, indicating that NOVAPRO® powder could be added to processed meat products to reduce costs without compromising product quality.
Keywords: beef frankfurters; exhibition swine; African swine fever; infectious disease; collagen powder